Setting up a New Library: Planning, Challenges, and Lessons Learned. A Case Study about Qatar National Library - Katia Medawar (15385784) (2021)
Prior to the opening of the Qatar National Library (QNL) in November 2017, the library went through an extensive planning and development process. This included constructing the building itself, which would house the collections, staff, and public spaces; testing the IT infrastructure; team building; processing newly acquired materials; and moving all the equipment, large and small, to the new building. This article focuses on the planning process for moving the library’s collections and covers the various steps taken to ensure success on opening day. It also describes the challenges faced during the planning process and after the move to the new building. While libraries do not move often, this article was written in the hopes of helping those who find themselves in this unique situation. Other Information Published in: International Information & Library Review License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1080/10572317.2021.1898757